Pengembangan Bahan Ajar Bahasa Arab Berbasis Keterampilan Berbahasa - Wa Erwita; Andi Abdul Hamzah (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Speaking skills are one of the fundamental aspects of language competence that play a central role in interpersonal communication, learning, and individual self-development in society. In the context of language learning, speaking skills not only reflect a person's linguistic ability, but also demonstrate maturity of thinking, social skills, and the capacity to participate actively in various communicative situations. UNESCO (2023) emphasizes that strengthening oral communication skills among students is very important to prepare them to face the challenges of the increasingly complex and dialogue-based world of work and global society. This teaching material development model is also driven by the use of technology and interactive multimedia, such as animated videos, to web-based e-modules. Recent studies have shown that teaching materials like this have been proven to improve students' maharah kalam (speaking), reading comprehension, and critical thinking skills in understanding Arabic texts more comprehensively